STAT3 inhibitors for cancer therapy: Have all roads been explored? - Fagard, Remi (Landes Bioscience, 2013)
The signal transducer and activator of transcription STAT3 is a transcription factor which plays a key role in normal cell growth and is constitutively activated in about 70% of solid and hematological cancers. Activated STAT3 is phosphorylated on tyrosine and forms a dimer through phosphotyrosine/src homology 2 (SH2) domain interaction. The dimer enters the nucleus via interaction with importins and binds target genes. Inhibition of STAT3 results in the death of tumor cells, this indicates that it is a valuable target for anticancer strategies; a view that is corroborated by recent findings of activating mutations within the gene. Yet, there is still only a small number of STAT3 direct inhibitors; in addition, the high similarity of STAT3 with STAT1, another STAT family member mostly oriented toward apoptosis, cell death and defense against pathogens, requires that STAT3-inhibitors have no effect on STAT1. Specific STAT3 direct inhibitors consist of SH2 ligands, including G quartet oligodeoxynucleotides (ODN) and small molecules, they induce cell death in tumor cells in which STAT3 is activated. STAT3 can also be inhibited by decoy ODNs (dODN), which bind STAT3 and induce cell death. A specific STAT3 dODN which does not interfere with STAT1-mediated interferon-induced cell death has been designed pointing to the STAT3 DBD as a target for specific inhibition. Comprehensive analysis of this region is in progress in the laboratory to design DBD-targeting STAT3 inhibitors with STAT3/STAT1 discriminating ability.